Managing Kubernetes resources using Helm : simplifying how to build, package, and distribute applications for Kubernetes - Block, Andrew; Dewey, Austin (Packt Publishing Ltd., 2022)
Containerization is one of the best ways to implement DevOps, and learning how to execute it effectively is an essential part of a developer's skillset. Kubernetes is the current industry standard for container orchestration. This book will help you discover the efficiency of managing applications running on Kubernetes with Helm. Starting with a brief introduction to Helm and its impact on users working with containers and Kubernetes, you'll delve into the primitives of Helm charts and their architecture and use cases. From there, you'll understand how to write Helm charts in order to automate application deployment on Kubernetes and work your way toward more advanced strategies. These enterprise-ready patterns are focused on concepts beyond the basics so that you can use Helm optimally, looking at topics related to automation, application development, delivery, lifecycle management, and security. By the end of this book, you'll have learned how to leverage Helm to build, deploy, and manage applications on Kubernetes.